Financial Freedom: The Role of Effective Financial Management and Investment Experience - Kusumawati, Fariyana; Kompyurini, Nurul (Journal of International Conference Proceedings, 2024)
The significance of this research is related to the methods used to achieve financial freedom through the role of effective financial management and investment experience for MSME players. This research aims to analyze financial freedom in terms of effective financial management and investment experience among MSMEs in Madura. The contribution of this research is to provide knowledge and understanding to MSME players about effective financial management and investment experience in an effort to achieve financial freedom.  This research is quantitative in type. MSME actors in the Madura region are the population in this study, while the sampling technique uses convenience sampling and data collecting techniques through distributing questionnaires. Data were processed using multiple linear regression analysis. The research results show that effective financial management influences financial freedom at a confidence level of 95% or an error rate of 5%. Meanwhile, investment experience has an influence on financial freedom at a confidence level of 90% or an error rate of 10%. Thus, effective financial management and investment experience play a good role in efforts to achieve financial freedom for MSMEs in Madura